2019
DOI: 10.1088/1367-2630/ab1c75
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying arbitrary-spin-wave-driven domain wall motion, the creep nature of domain wall and the mechanism for domain wall advances

Abstract: Domain wall motion (DWM) by spin waves (SWs) in different waveforms in a magnetic nanostripe is investigated via micromagnetic simulations. Diversified DWMs are observed. It is found that SW harmonic drives DWM most efficiently and irregular SW may cause abnormal excitation spectrum for DWM in the low-frequency range. We prove that SW harmonic is the basic element when interacting with DW and causes simple creeping motion of DW (i.e. forward propagation of DW accompanied with oscillation) with the same frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…The [31] shows that the spin wave assistance can enhance the current driven magnetic domain wall movement, so it can be used to reduce driving current. In addition, the previous research has shown that spin wave driving the magnetic domain walls movement depends on its amplitude and frequency [32][33][34]. In detail, the speed of spin wave driven domain wall movement is linearly dependent on the amplitude of the spin wave, but nonlinearly dependent on the frequency of the spin wave.…”
Section: Resultsmentioning
confidence: 96%
“…The [31] shows that the spin wave assistance can enhance the current driven magnetic domain wall movement, so it can be used to reduce driving current. In addition, the previous research has shown that spin wave driving the magnetic domain walls movement depends on its amplitude and frequency [32][33][34]. In detail, the speed of spin wave driven domain wall movement is linearly dependent on the amplitude of the spin wave, but nonlinearly dependent on the frequency of the spin wave.…”
Section: Resultsmentioning
confidence: 96%
“…To understand the origin of the forward shifting of SW phase, propagations of SW through a single head-to-head TW have been mapped [4,19], see figure 13. It is found that SW can propagate with larger velocity inside of TW (see the black solid lines) than in uniform magnetization (see the black dashed lines).…”
Section: Resultsmentioning
confidence: 99%
“…where M is the local magnetization vector, H eff is the effective field, γ = μ 0 eg 2m e is the gyromagnetic ratio, and α is the In order to model infinite length of the nanostip as well as to avoid possible distortion of the nanostripe, the left-end and right-end edges are artificially pinned [4]. Meanwhile, to prevent SW reflection from the two ends, each end within 100 × 40 × 5 nm 3 is assigned with increased α which varies linearly from 0.01 to 1 [17,55] such that the SW are sufficiently damped near edges.…”
Section: Simulation Detailsmentioning
confidence: 99%
See 2 more Smart Citations